INTEGRASI AKUNTANSI MANAJEMEN STRATEGIS DALAM MANAJEMEN RISIKO DAN KINERJA KEUANGAN BANK: SEBUAH KAJIAN LITERATUR SISTEMATIS - Dermawan, Irvan; Surbakti, Lidya Primta (LP2M Politeknik Jambi, 2025)
The banking industry operates in an environment characterized by high uncertainty, increasing regulatory demands, and rapid technological transformation, exposing banks to various risks that may threaten financial stability and performance. This study conducts a systematic literature review to examine how the integration of Strategic Management Accounting (SMA) and Enterprise Risk Management (ERM) can strengthen risk-based decision-making and enhance the financial performance of banks. Using the PRISMA protocol, relevant studies published between 2010 and 2025 were identified from major academic databases and synthesized thematically. The review reveals that SMA provides forward-looking strategic information—such as cost structures, profitability analysis, and scenario projections—that enriches ERM’s risk assessment and mitigation processes. ERM, in turn, offers a structured governance framework that ensures consistent utilization of SMA information across decision-making levels. The integration of SMA and ERM is found to positively influence key financial indicators, including ROA, ROE, BOPO, and NPL, through improved efficiency, enhanced internal control, and more accurate risk evaluation. However, existing studies tend to discuss SMA and ERM separately, with limited empirical evidence on their combined effect in the banking sector. This study contributes by proposing an integrated conceptual model and highlighting future research opportunities to empirically validate SMA–ERM integration, particularly in the context of digital banking risks.